The brave horse brother - Parker, Vic (United Kingdom : Miles kelly, 2014)
Meet some of the noblest horses in fiction in this collection of classic stories. Featuring much loved authors such as James Baldwin and Andrew Lang, these exciting tales are brought to life with charming illustrations.
location: 3B
Keywords: Fiction book